2018
DOI: 10.5812/aapm.80184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose Containing Crystalloid Infusion on Maternal Hemodynamic Status After Spinal Anesthesia for Cesarean Section

Abstract: BackgroundDespite preventive strategies, hypotension is the most common complication of spinal anesthesia in cesarean section.ObjectivesThe aim of this study was to assess the effect of glucose-containing crystalloid infusion on maternal hemodynamic status after spinal anesthesia for cesarean section.MethodsIn this prospective, randomized, double-blind clinical trial, 80 parturients undergoing elective cesarean section with spinal anesthesia were studied. In group A (n = 40) ringer with 1% glucose solution (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…They found a shorter duration of hypotension in the isobaric group compared to the hyperbaric bupivacaine group (1.67 ±7.8 min vs 7.4 ± 12.5 min, P = 0.004) and lower ephedrine requirements in the isobaric bupivacaine group than in the hyperbaric bupivacaine group (2.4 mg ± 6.6 mg vs 5.3 ± 10.7 mg, P = 0.006). 20 The results of our study are also inconsistent with those of a randomized controlled trial conducted at the Cantonal Hospital, which showed a greater reduction in MAP in the hyperbaric group than in the isobaric group. This difference might be due to the difference in the volume of bupivacaine used (10 mg), additive intrathecal fentanyl (15 µg), positioning, height of parturients, and differences in the study population.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They found a shorter duration of hypotension in the isobaric group compared to the hyperbaric bupivacaine group (1.67 ±7.8 min vs 7.4 ± 12.5 min, P = 0.004) and lower ephedrine requirements in the isobaric bupivacaine group than in the hyperbaric bupivacaine group (2.4 mg ± 6.6 mg vs 5.3 ± 10.7 mg, P = 0.006). 20 The results of our study are also inconsistent with those of a randomized controlled trial conducted at the Cantonal Hospital, which showed a greater reduction in MAP in the hyperbaric group than in the isobaric group. This difference might be due to the difference in the volume of bupivacaine used (10 mg), additive intrathecal fentanyl (15 µg), positioning, height of parturients, and differences in the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference from our results might be due to the different doses of bupivacaine and the additives (15 µg fentanyl). 20 Another study by Helill et al revealed higher levels of sensory blockage in an isobaric bupivacaine group than in a hyperbaric bupivacaine group. A sensory block up to the T4 level was seen in three (6%) patients in the isobaric group and none in the hyperbaric group (P = 0.001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gousheh et al (14) have stated the use of crystalloid solutions compared with colloid ones would stabilize blood pressure and heart rate after spinal anesthesia during cesarean section. This issue was more prominent when another author added glucose to the crystalloid solution (15). In contrast, another study has revealed that infusion of phenylephrine to prevent overt either hypotension or bradycardia was associated with better symptom (nausea and vomiting) control and also resulted in favorable neonatal blood gas outcomes (16).…”
Section: Discussionmentioning
confidence: 99%
“…It may be prepared as an isobaric or hyperbaric solution. Alterations in the baricity of spinal anesthetic solutions influence the distribution and hemodynamic parameters in the subarachnoid space ( 5 , 6 ). This may influence the onset, duration, and severity of sensory block and any side effects ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%